2009
DOI: 10.1039/b822353j
|View full text |Cite
|
Sign up to set email alerts
|

Redox active donor-substituted punicin derivatives

Abstract: The redox active plant material punicin from Punica granatum, 2-hydroxy-1-(pyridinium-1-yl)-5-olate, and some derivatives were modified by substitution with 2-oxochromen-4-olate moieties to give donor-substituted molecules which form distinct types of atropisomeric mesomeric betaines and tetrapolar substances. Oxidation to new negatively-charged solvatochromic quinones was achieved on treatment of these betaines with CAN, taking advantage of the stabilizing properties of the electron-donating 2-oxochromen-4-ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…The case of Diels ' betaine ( 16 )[25], which has also been identified as the alkaloid punicine from Punica granatum ,[26] is interesting as it could principally occur in two tautomeric forms 16a / 16b , of which 16a is a conjugated mesomeric betaine, isoconjugate to an odd alternant hydrocarbon anion (class 1), and 16b is a cross‐conjugated betaine, isoconjugate to an odd, alternant hydrocarbon monoanion (class 9). The more recently reported betaine 17 [9c] combines a 1,3‐diketoenolate anion with an imidazolium cation.…”
Section: Resultsmentioning
confidence: 99%
“…The case of Diels ' betaine ( 16 )[25], which has also been identified as the alkaloid punicine from Punica granatum ,[26] is interesting as it could principally occur in two tautomeric forms 16a / 16b , of which 16a is a conjugated mesomeric betaine, isoconjugate to an odd alternant hydrocarbon anion (class 1), and 16b is a cross‐conjugated betaine, isoconjugate to an odd, alternant hydrocarbon monoanion (class 9). The more recently reported betaine 17 [9c] combines a 1,3‐diketoenolate anion with an imidazolium cation.…”
Section: Resultsmentioning
confidence: 99%
“…4‐Hydroxycoumarin derivatives have shown a variety of pharmaceutical activity with the latent ability to exert non‐covalent interactions with various active sites in organisms, such as anticoagulant, insecticidal, antihelminthic, hypnotic, and antifungal activity, phytoalexin production, and human immunodeficiency virus protease inhibition [8–11]. Our previous research also showed the potential antibacterial activity of some 4‐hydroxycoumarin derivatives [12].…”
Section: Introductionmentioning
confidence: 90%
“…4-Hydroxycoumarin derivatives have shown a variety of pharmaceutical activity with the latent ability to exert noncovalent interactions with various active sites in organisms, such as anticoagulant, insecticidal, antihelminthic, hypnotic, and antifungal activity, phytoalexin production, and human immunodeficiency virus protease inhibition. [8][9][10][11] Our previous research also showed the potential antibacterial activity of some 4-hydroxycoumarin derivatives. [12] Because coumarin derivatives include umbelliferone (7-hydroxycoumarin), aesculetin (6,7-dihydroxycoumarin), herniarin (7-methoxycoumarin), psoralen and imperatorin, [13] it is still unclear what kind of coumarin derivatives have more potent antibacterial activity.…”
Section: Introductionmentioning
confidence: 99%
“…Coumarin (2H-chromen-2-one) derivatives, containing aromatic d-lactones system, are an important class of heterocycles that have attracted significant importance in the field of organic and natural product chemistry [8][9][10][11]. For example, biscoumarin and its derivatives have received considerable attention in the past few years for their versatile biological and medical activities because of the ease of fine-tuning the aromatic ring with different substituents on leading to multiple chemical modifications and activities such as antioxidant, anti-inflammatory, antibacterial and anticancer [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Methicillin-resistant S. aureus (MRSA) is the cause of most antibiotic resistant healthcare associated infections, because it spreads rapidly and cause illness more severe, which further leads to mortality and morbidity rates of patients affected by MRSA are high [4,5], and the related proportion of such cases increased significantly [6,7]. In addition, the emergence of MRSA with decreased susceptibility to vancomycin, which is customarily used as the most effective antibiotic to treat for MRSA, induced to the urgent necessity of developing new antimicrobials.Coumarin (2H-chromen-2-one) derivatives, containing aromatic d-lactones system, are an important class of heterocycles that have attracted significant importance in the field of organic and natural product chemistry [8][9][10][11]. For example, biscoumarin and its derivatives have received considerable attention in the past few years for their versatile biological and medical activities because of the ease of fine-tuning the aromatic ring with different substituents on leading to multiple chemical modifications and activities such as antioxidant, anti-inflammatory, antibacterial and anticancer [12][13][14].…”
mentioning
confidence: 99%